Hubungan Gaya Belajar dengan Nilai Hasil Ujian Modul Sistem Gastro-intestinal, Hepatobilier Dan Pankreas Pada Mahasiswa Angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi - Abay, Novita A.; Wungouw, Herlina I. S.; Berhimpon, Siemona (e-Biomedik, 2018)
Abstract: In an educational institution, achievement or performance of study is an important indicator to measure the success of teaching-learning process. Learning factors that can influence students’ grades are internal and external factors. This study was aimed to obtain the relationship between learning style and students’ grades in the gastrointestinal system, hepatobiliary, and pancreas module. This was an analytical study with a cross sectional design. Respondents were 90 students of batch 2016. Data were obtained by filling the learning style questionnaire and students’ grades were obtained from the Academic Department. Data were analyzed by using the chi-square test. The chi-square test on dominant learning style showed a P value of 0.989 meaning there was no significant relationship between dominant learning style and the grades, meanwhile on combined learning style the P value was 0.410 which also meant that there was no relationship between learning style and the grades. Conclusion: There was no relationship between learning style and students’ grades in the gastrointestinal system, hepatobiliary, and pancreas module among students of Faculty of Medicine, Sam Ratulangi University.Keywords: learning style, students’ grades Abstrak: Dalam suatu lembaga pendidikan, prestasi belajar merupakan indikator penting untuk mengukur keberhasilan proses belajar mengajar. Faktor belajar yang dapat memenga-ruhi hasil belajar mahasiswa ialah faktor internal dan faktor eksternal. Penelitian ini bertujuan untuk untuk mengetahui hubungan gaya belajar dengan nilai hasil ujian modul sistem gastrointestinal, hepatobilier dan pankreas. Jenis penelitian ialah analitik dengan desain potong lintang. dengan jumlah sampel sebanyak 90 orang mahasiswa angkatan 2016. Data didapatkan melalui pengisian kuesioner gaya belajar dan data nilai didapatkan dari bagian akademik. Uji analisis pada penelitian ini menggunakan uji chi-square. Hasil penelitian dengan uji chi-square pada gaya belajar dominan didapatkan nilai P=0,989 yang menunjukkan tidak terdapat hubungan bermakna antara gaya belajar dominan dengan hasil ujian, sedangkan untuk gaya belajar gabungan didapatkan nilai P=0,410 artinya tidak terdapat hubungan gaya belajar dengan hasil ujian. Simpulan: Tidak terdapat hubungan antara gaya belajar dengan nilai hasil modul gastrointestinal, hepatobilier, dan pankreas pada mahasiswa angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi.Kata kunci: gaya belajar, hasil belajar